MINTAQADA INVESTITSION SALOHIYATNI OSHIRISHNING XORIJIY MAMLAKATLAR TAJRIBASI (Marketing Journal, 2026)
AbstractThis article examines the foreign experience of enhancing regional investmentpotential. Particular attention is paid to institutional mechanisms, investmentpromotion tools, and the formation of a favorable investment climate in developed andemerging economies. The study systematizes effective approaches to increasingregional investment capacity and substantiates the possibility of their application innational economic conditions. The findings contribute to the development ofmethodological and practical recommendations for strengthening regional investmentattractiveness.Keywords: investment potential, regional development, investmentattractiveness, institutional factors, foreign experience, investment climate, economicdevelopment.